Prognostic Impact of Sarcopenia on Clinical Outcomes in Malignancies Treated With Immune Checkpoint Inhibitors: A Systematic Review and Meta-Analysis - Li, Shuluan; Wang, Tianyu; Tong, Gangling; Li, Xiaoyu; You, Danhui; Cong, Minghua (Frontiers in Oncology, 2021)
Background: Whether sarcopenia has an impact on the clinical outcomes of patients with malignant neoplasms received immune checkpoint inhibitors(ICIs) is not clear. The aim of this study is to evaluate the effect and survial of ICIs on malignancies with sarcopenia. Methods: We systematically searched the related studies in Pubmed,Embase, and Cochrane Library up to March 2021 according to inclusion and exclusion criteria. The hazard ratio(HR)corresponding 95% confidence interval(CI) of overall survival(OS) and progression-free survival(PFS) by univariate and multivariate analysis, the odds ratio(OR)corresponding 95% CI of disease control rate(DCR)and objective repose rate(ORR)as well as immune-related adverse events (irAEs) were collected and analysed by using the Revman5.4software. Study heterogeneity and sensitivity was assessed. Results: There are a total of 14 studies including 1448 patients consisting of lung cancer, melanoma, renal cell carccinoma, urothelial carccinoma, gastrointestial, head and neck and others. Patients with sarcopenia at pre-immunotherapy had poorer PFS and OS by univariate and multivariate analyses, HRs and corresponding 95% CI of PFS were 2.01(58-2.54, p<0.00001) and 1.51(1.23-1.86, p<0.00001) respectively. And OS with HRs and corresponding 95% CI were 1.70(1.39-2.08, p<0.00001) and 1.62 (1.26-2.10, p=0.0002) respectively. Patients evolving sarcopenia during the treatment showed poor PFS and OS. Also patients with sarcopenia had worse ORR(OR 0.46, 95%CI 0.26-0.81, p=0.007) and DCR(OR 0.42, 95%CI 0.27-0.65, p=0.0001), However, incidence of irAEs in patients with sarcopenia did not increase (OR 0.59,95%CI0.29-1.19,p=0.14). Subground analysis showed in SMI group, the ORR, DCR,PFS and OS were all related to sarcopenia. Conclusions: Malignancies with sarcopenia at pre-Immunotherapy or at follow-up visit had poorer clinical outcomes, and sarcopenia was a poor predictive factor when received ICIs Immunotherapy.